Global Symposium on Millimeter-Waves (GSMM) 2015
DOI: 10.1109/gsmm.2015.7175436
|View full text |Cite
|
Sign up to set email alerts
|

Broadband antenna array with low cost PCB substrate for 5G millimeter wave applications

Abstract: In this paper, a novel broadband antenna array is presented. The radiating element is a unique via-fed U-shaped patch element with a distribution network based on offset stripline technology. The feed position has been deliberately designed for optimized matching taking into account the design rules of a low cost PCB mass production technology. The radiating element has a 3-dB beam-width of ±30 degrees in both planes making it suitable for beam steering. To show the validity of the approach, a 2×2 array protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The superstrate layer is employed above the antenna array-2 to increase the antenna gain and efficiency as shown in Figure 1d. An inexpensive Rogers RO4350B material is used as a superstrate layer with a thickness of 1.524 mm, dielectric constant of 3.66, and loss tangent of 0.004 due to its property of low metallic losses at the MMW band [32,33]. The air gap between the superstrate layer and the antenna is usually taken to be about a half wavelength.…”
Section: Array-2 With Superstratementioning
confidence: 99%
“…The superstrate layer is employed above the antenna array-2 to increase the antenna gain and efficiency as shown in Figure 1d. An inexpensive Rogers RO4350B material is used as a superstrate layer with a thickness of 1.524 mm, dielectric constant of 3.66, and loss tangent of 0.004 due to its property of low metallic losses at the MMW band [32,33]. The air gap between the superstrate layer and the antenna is usually taken to be about a half wavelength.…”
Section: Array-2 With Superstratementioning
confidence: 99%
“…While microstrip antennas have been the subject of many intensive works for decades [20][21][22][23][24], they have been considered in some research efforts reported in the past few years on antenna design aspect of the newly emerging mmW wireless communications [19,[25][26][27][28][29][30][31][32]. Antennas in [19] and [25][26][27][28] are mainly designed to operate in one of the target frequency bands, as listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…This array provided a bandwidth of 5 GHz and a maximum gain of 16 dBi, but the element spacing is larger than one wavelength, i.e., 12 mm, at the center frequency. In [32], Huawei Technologies presented a LMDS 2 × 2 broadband antenna array composed of unique viafed U-shaped patch elements, separated by about 0.6 wavelength at 27 GHz, and a stripline distribution network. It provided a 7 GHz bandwidth and a maximum gain of 11 dBi.…”
Section: Introductionmentioning
confidence: 99%